2005
DOI: 10.1086/430614
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of SelectedMycobacterium tuberculosisClinical Isolates in the Rabbit Model of Meningitis Is Dependent on Phenolic Glycolipid Produced by the Bacilli

Abstract: Infection with Mycobacterium tuberculosis in humans results in active disease in approximately 10% of immune-competent individuals, with the most-severe clinical manifestations observed when the bacilli infect the central nervous system (CNS). Here, we use a rabbit model of tuberculous meningitis to evaluate the severity of disease caused by the M. tuberculosis clinical isolates CDC1551, a highly immunogenic strain, and HN878 or W4, 2 members of the W/Beijing family of strains. Compared with infection with CDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
182
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(197 citation statements)
references
References 43 publications
11
182
2
2
Order By: Relevance
“…A recent study suggests that patients infected with Beijing strains are more likely to develop extrathoracic tuberculosis than people infected with strains of other lineages (14). This observation is consistent with the results obtained in a rabbit model with the Beijing strain HN878, which was found more likely to infect the brain and to disseminate (15). A recent study in Vietnam pointed out that the typical lineage of Beijing genotype strains is more frequently found in patients who received a Bacillus Calmette-Guérin vaccination.…”
supporting
confidence: 90%
“…A recent study suggests that patients infected with Beijing strains are more likely to develop extrathoracic tuberculosis than people infected with strains of other lineages (14). This observation is consistent with the results obtained in a rabbit model with the Beijing strain HN878, which was found more likely to infect the brain and to disseminate (15). A recent study in Vietnam pointed out that the typical lineage of Beijing genotype strains is more frequently found in patients who received a Bacillus Calmette-Guérin vaccination.…”
supporting
confidence: 90%
“…Several in vivo models to study mycobacterial pathogenesis exist, such as rabbits, guinea pig, and mice (Be et al, 2012; Be, Klinkenberg, Bishai, Karakousis, & Jain, 2011; Skerry et al, 2013; Tsenova et al, 2005; Tucker et al, 2016; van Well et al, 2007; Zucchi et al, 2012). However, none of these models could demonstrate the course of events during mycobacterial trafficking across the BBB in a living host.…”
Section: Introductionmentioning
confidence: 99%
“…Why do clinical isolates of M.tb present different cell wall rearrangements than the widely studied M.tb laboratory strains Erdman, H 37 R v , and H 37 R a ? In this context, hypervirulent M.tb strains of the Beijing family (Tsenova et al, 2005) are shown to contain large amounts of triglycerides (Reed et al, 2007), and some of them also contain the PGL-TB (Reed et al, 2004). M.tb clinical isolates deficient in ManLAM and PIMs surface exposure, but presenting in their cell wall large quantities of triglycerides, PGL-TB, and dimycocerosates, are also shown to have reduced phagocytosis but faster intracellular growth rate in human macrophages (Torrelles et al, 2008b).…”
Section: Lipoglycoconjugates Of the M Tuberculosis Cell Wallmentioning
confidence: 99%